Analisis Hukum Islam Dalam Pengelolaan Zakat, Infaq Dan Sedekah Pada Rumah Amal Salman Garut - Izzan, Ahmad; Febrianty, Vina (Jurnal Hukum Ekonomi Syariah, 2023)
Abstract In the midst of economic problems, zakat has emerged as an instrument for economic development and alleviation of poverty for the people in the regions. Zakat has many advantages over the existing conventional fiscal instruments. Many thoughts and theories put forward by experts in the context of tackling the problem of poverty. However, not all theories can be put into practice and can overcome poverty. It is hoped that professional zakat management and productive utilization will be able to contribute to poverty alleviation. (Abidah, 2016) This research wants to answer: what is meant by Islamic law? How is the management of zakat, infaq, and alms at the Salman Garut Charity House? How is the analysis of Islamic law in the management of zakat, infaq, and alms at the Salman Garut Charity House, with the objectives: 1.) To find out what is meant by Islamic law? 2.) To find out how the management of zakat, infaq and alms at the Salman Garut Charity House; 3.) To find out how the analysis of Islamic law in the management of zakat, infaq, and alms at the Salman Garut Charity House. To achieve the above objectives the research method used is descriptive method with a qualitative approach. As for data collection techniques using interviews (interviews), observation and documentation with Rumah Aml Salman employees as primary data. While secondary data is obtained by direct visits to the object of research, from websites, books, journals, magazines, theses, and other sources related to this problem. From the results of the study, it can be concluded that, apart from being audited by a public accountant, Salman Amal House is also accredited A and has received the title of sharia opinion "According to Sharia" from the Ministry of Religion of the Republic of Indonesia. The management of zakat, infaq, and alms at Rumah Amal Salman is accredited A and has received the title of “According to Sharia” sharia audit opinion from the Ministry of Religion of the Republic of Indonesia, in carrying out its policies, Salman Amal House always communicates with the sharia supervisory board because it is certified by the MUI. Rumah Amal Salman won an unqualified financial audit opinion (WTP) for 5 consecutive years from 2017 to 2021. Keywords: Islamic law, management of zakat, infaq, and alms